STRUCTURE OF CONTROL SYSTEMS VODYDLYA AGRICULTURAL ENTERPRISE - , Н. А. (Municipal economy of cities. Series: «Economy science», 2013)
We consider the need for automatic monitoring stations (ASA) of large agricultural enterprises. It may be used in functional and numerical inspection. The features of the controlled parameters of such objects, the primary purpose and structure of ASA. The details of implementation to the example of large livestock farms.